The Effect of Structure Dyadic Method on Toward Students Reading Comprehension - Widuri, Elvi; Asi Lestari, Putri; Ayu, Citra (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This experimental research was carried out on Grade Nine students at MTS PP. Mu'allimin Muhammadiyah Bangkinang City in the 2023/2024 learning year. This study aims to find out the effect of the Dyadic Structure Method on students' reading comprehension. This type of research uses quasy-experimental by comparing two groups, namely the experimental class and the control class. The sample used was class IX A which consisted of 30 students as the experimental group and class IX B which consisted of 30 students as the control group. The research instrument was a reading comprehension test which consisted of 20 multiple choice questions. This study used a purposive sampling technique in which the researcher chose the class category to be examined. Data were analyzed using the IBM SPSS 23 program. Based on the data analysis, the researchers obtained the results, namely the average value of the experimental class was 94.00 and the average value of the control class was 84.00. the researcher uses the T-test with the formula If T count > T table, the hypothesis is accepted (Ha). If T count < T table, the hypothesis is rejected (ho). From the calculation results, it was found that tcount = 9.878 > t-table 5.471 in the degree of freedom (58) and the level of significance (2-tailed) was 0.000 <0.05 (5%), meaning that Ha was accepted. This indicates that there is a significant effect of the structured dyadic method on students' reading skills in MTS PP. Mu'allimin Muhammadiyah Bangkinang city.